Authentic Assessment in Examining EFL Students’ Writing - Hitimala, Hardianto; Wirza, Yanty (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
This writing intended to explore authentic assessment in teaching EFL writing, focusing on how the authentic assessment is presented in writing, the problem of the implementation, as well as the effectiveness. This is a literature review writing that examines previous articles. According to previous studies, some teachers have used authentic assessment to evaluate their students’ writing skills, but they have faced some challenges such as lack of time and resources to implement all kinds of authentic assessment. Authentic assessment is a powerful way to measure student writing because it allows students to write about realistic situations that suit their needs, and it can also enhance their writing abilities, motivation, enthusiasm, and desire to write